The Moderating Role of Group Lending on the Relationship between Microfinance and Poverty in Pakistan - Rossazana, Ab-Rahim; Saif-Ul-Mujahid, Shah (Human Resource Management Academic Research Society (HRMARS), 2019)
This paper aims to investigate the moderating effect of group lending on the relationship between poverty and non-governmental (NGO) microfinance in Northern Pakistan, Khyber Pukhtun Khawa. Quantitative primary data is collected from 297 borrowers of NGOs microfinance. The partial least squares-structural equation modelling moderating role of group lending between the microfinance and poverty is estimated through structural equation model and for the purpose of calculation Smart PLS is used. The results show that the group lending has significant impact on relationship between poverty and microfinance and played a major role in mitigating moral hazard among the respondents. The finding suggests that the group lending approach should be adopted in the loan distribution especially in rural areas.